Green Products, Halal Certification, and Halal Awareness: Case Study of Purchase Decision on Oriflame Products - Nisa, Ainul Hayatin; Muhaimin, Muhaimin; Syarqawie, Fithriana; Akbar, Ilham; Rimayanti, Rimayanti (Institut Agama Islam Negeri Kendari, 2024)
This study examines the influence of green products, halal certification, and halal awareness on the purchasing decisions of Oriflame products in Banjarmasin. With growing environmental concerns and increasing awareness of halal consumption, Muslim consumers are now considering both the eco-friendliness and the halal status of products before making purchasing decisions. This research uses a quantitative approach, collecting data through questionnaires distributed to 96 respondents who are Oriflame consumers in Banjarmasin. The data were analyzed using multiple linear regression with SPSS 25. The results show that green products, halal certification, and halal awareness have a positive and significant effect on purchasing decisions, both individually and collectively. Specifically, halal awareness was found to be the most influential factor in shaping purchasing decisions. The study also reveals that while green products are essential for consumers concerned about the environment, halal certification plays a crucial role in ensuring the product’s compliance with Islamic law, fostering trust among Muslim consumers. The findings suggest that companies marketing to Muslim consumers should emphasize both the sustainability of their products and their halal certification to meet the growing demand for ethically and religiously compliant goods. This research contributes to understanding consumer behavior in the halal product market, particularly in Indonesia, and offers valuable insights for businesses seeking to target eco-conscious Muslim consumers.